DESIGN OF A 5-STOREY OFFICE BUILDING USING REINFORCED CONCRETE STRUCTURE - Yordania Agusti; Muhammad Febrian Ardiyansah; Atha Fauziah; Galang Nur Muhammad; Nor Hidayati (Universitas Islam Nahdlatul Ulama Jepara, 2026)
The design of a five-storey office building using a reinforced concrete structural system aims to produce a strong, stable, and earthquake-resistant building in accordance with national standards. This study was carried out through primary data collection from soil cone penetration tests and secondary data from relevant literature and design codes. Structural analysis was conducted using SAP2000 software to determine internal forces, moments, and deflections of structural components. The applied loads included dead, live, rain, and seismic loads, referring to SNI 1726:2019, SNI 2847:2019, and SNI 1727:2020. The results indicate that the optimal floor and roof slab thicknesses are 120 mm and 100 mm, respectively; main beams are sized 25×45 cm with 3D22–2D22 reinforcement; columns are 50×50 cm with 6D22 bars; and the bore pile foundation has a 0.35 m diameter and 9 m depth. All structural components meet the strength and safety requirements specified by SNI standards. This design serves as a reference for efficient, safe, and earthquake-resistant office building planning in Indonesia. PERENCANAAN GEDUNG KANTOR 5 LANTAI MENGGUNAKAN STRUKTUR BETON BERTULANGPerencanaan struktur gedung kantor lima lantai menggunakan sistem beton bertulang bertujuan untuk menghasilkan rancangan bangunan yang kuat, stabil, dan aman terhadap beban gempa sesuai standar nasional. Penelitian ini dilakukan melalui tahapan pengumpulan data primer berupa hasil uji sondir tanah serta data sekunder dari literatur dan peraturan teknis. Analisis struktur dilakukan dengan perangkat lunak SAP2000 untuk menghitung gaya dalam, momen, serta lendutan pada setiap elemen struktur. Beban yang diperhitungkan meliputi beban mati, beban hidup, beban hujan, serta beban gempa berdasarkan SNI 1726:2019, SNI 2847:2019, dan SNI 1727:2020. Hasil perencanaan menunjukkan bahwa pelat lantai dan atap memiliki tebal optimal 120 mm dan 100 mm, balok induk berukuran 25×45 cm dengan tulangan 3D22–2D22, kolom 50×50 cm dengan tulangan 6D22, serta pondasi bore pile berdiameter 0,35 m dan panjang 9 m. Berdasarkan hasil analisis, seluruh elemen struktur memenuhi kriteria kekuatan dan keamanan sesuai ketentuan SNI. Perencanaan ini diharapkan dapat menjadi acuan dalam merancang gedung kantor bertingkat yang efisien, aman, dan tahan gempa di Indonesia.